Significance of indeterminate third-generation hepatitis C virus recombinant immunoblot assay. - Pawlotsky, J M (1996)
Indeterminate hepatitis C virus (HCV) third-generation recombinant immunoblot assay (RIBA3.0; Ortho Diagnostic Systems) patterns were arbitrarily defined by the manufacturer as the detection of only one antibody out of the four that were sought, namely, c100 (NS4 encoded), c22 (core encoded), c33c (NS3 encoded), and NS5 (NS5 encoded). The aims of the present study were (i) to determine the prevalence of indeterminate RIBA3.0 patterns in patients consecutively tested for anti-HCV antibodies in a university hospital; (ii) to evaluate the significance of these patterns in terms of viral replication, liver disease, and risk factors for HCV; and (iii) to get an insight into the mechanism underlying this peculiar immune response. Among 3,074 serum samples consecutively tested for anti-HCV antibodies, 588 were found to be positive by screening assays. Fifty-nine of them (10%) were RIBA3.0 indeterminate and were compared with 59 RIBA3.0-positive ones. Thirty-one RIBA3.0-indeterminate and 53 RIBA3.0-positive serum samples were HCV RNA positive by PCR (53 versus 90%; P < 10(-6). RIBA3.0-indeterminate and RIBA-3.0-positive patients with positive PCR results were not significantly different for the prevalence of risk factors for HCV infection and elevated serum alanine aminotransferase activities. Immunosuppression, attributable to coexisting human immunodeficiency virus infection, organ transplantation, or the administration of immunosuppressive drugs, was significantly more frequent in PCR-positive, RIBA3.0-indeterminate patients than in PCR-negative, RIBA3.0 indeterminate patients (P < 0.001) and PCR-positive patients with a positive RIBA3.0 result (P < 0.01). The distribution of HCV genotypes did not differ significantly between HCV RNA-positive patients with indeterminate or positive RIBA3.0 results. In conclusion, the prevalence of indeterminate RIBA3.0 patterns in virology laboratories is about 10%; in about half of these patients HCV replication is detected by PCR; the main factor responsible for indeterminate RIBA3.0 patterns could be immunosuppression, whereas HCV genotypes do not seem to play major role.